128k views
1 vote
I need help it doesn’t make any sense to me

I need help it doesn’t make any sense to me-example-1
User Zhe Zhang
by
5.0k points

1 Answer

2 votes

Given:


\begin{gathered} 3x+3y=3\ldots\ldots(1) \\ y=-(1)/(2)x+2\ldots\ldots(2) \end{gathered}

Multiply by 6 into equation (2) as,


\begin{gathered} 6y=-3x+12 \\ 3x+6y=12\ldots\text{.}\mathrm{}(3) \end{gathered}

Now, (1) - (3), then


\begin{gathered} 3x+3y-6y-3x=3-12 \\ -3y=-9 \\ 3y=9 \\ y=3 \end{gathered}

Hence, the value of y=3.

User GMA
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.